Hygienic practices, bacteriological quality of cow milk and its public health importance along the dairy value chain in Sidama High Lands of southern Ethiopia - Zewdu, M. (Addis Ababa University, 2015)
Milk is an important source of nutrients to human and animals, but due to its high water activity and nutritional value, it serves as an excellent medium for growth of many kinds of microorganisms under suitable conditions. The present cross sectional study was conducted to assess hygienic practices, determination of bacterial quantity of milk, isolation and identification of bacterial pathogens in milk and to determine antimicrobial susceptibility of the major isolate at each critical control points throughout the value chain in Arbegona, Bensa and Bona districts, Sidama zone from November 2014 to May 2015. A total of 120 respondents were interviewed and subsequently, 166 milk samples were collected for laboratory analysis including bacterial load assessment and isolation and identification of bacteria. Aerobic mesophilic bacterial counts (AMBC) and coliform counts (CC) from milk were conducted. Isolation and identification of the bacteria in the milk was also conducted following standard methods. Results showed that, majority of small-dairy holders were males, managing their cattle in unclean environments and practicing extensive grazing system on communal grazing area. The mean aerobic mesophilic bacterial counts of raw milk samples analyzed were 5.86 log10 cfu/ml (udder), 8.25 log10 cfu/ml (bucket) and 9.31 log10 cfu/ml (marketed milk container). The mean coliform counts were 3.61 log10 cfu/ml (udder), 5.47 log10 cfu/ml (bucket) and 7.47 log10 cfu/ml (marketed milk container). The increment of both counts at each critical control points was observed statistically significant (P=0.000) and there was no significant variation between districts (P=0.976) for AMBC and (P=0.795) for CC. According to international standards of raw milk quality, both the AMBC and CC have values above the upper limits set. In the course of this study, the frequent bacterial pathogens isolated from raw milk samples taken from different critical points include: Staphylococcus spp., Streptococcus spp., Corynebacterium spp., Bacillus spp., and coliforms. Of total isolates, 15 were tested for susceptibility to different eight antimicrobial discs; Gentamycin, Chloroamphenicol, Vancomycine and Kanamycin were the most effective antibiotics where by 93.1%, 75.8%, 72.4% and 58.6%, respectively.